Community Service: Education and Service Learning for Micro Business's Parachurch - Dirgantara Dahana Mokoginta; Gesti Memarista; Annisa Alfa Setyawan; Visi Saujaningati Kristyanto; Natalia Kristina (Sewagati, 2022)
During the restrictions on community activities due to the COVID-19 pandemic, GKI Emaus Surabaya urges church congregations to worship at home online and severely restricts church attendance. As a result, the micro-business community in the church experienced a significant decline in income. The community relies heavily on large numbers of the congregation in the church to sell the products optimally. This service-learning activity was held to help the GKI Emaus Surabaya micro-business community to be able to perform financial records more accurately with the help of Microsoft Excel so that the micro-business community can maximize capital during this difficult time. Activities are carried out virtually in the form of webinars and assistance in preparing financial records. After this activity, participants stated that they had gained a better understanding of the importance of detailed financial records and could use the basic features of Microsoft Excel for financial records. The target of this activity is to make participants familiar with the use of Microsoft Excel for financial recording purposes.